Alleviation of secondary brain injury, posttraumatic inflammation, and brain edema formation by inhibition of factor XIIa. Issue 1 (December 2017) - Hopp, Sarah; Nolte, Marc; Stetter, Christian; Kleinschnitz, Christoph; Sirén, Anna-Leena; Albert-Weissenberger, Christiane
Abstract Background Traumatic brain injury (TBI) is a devastating neurological condition and a frequent cause of permanent disability. Posttraumatic inflammation and brain edema formation, two pathological key events contributing to secondary brain injury, are mediated by the contact-kinin system. Activation of this pathway in the plasma is triggered by activated factor XII. Hence, we set out to study in detail the influence of activated factor XII on the abovementioned pathophysiological features of TBI. Methods Using a cortical cryogenic lesion model in mice, we investigated the impact of genetic deficiency of factor XII and inhibition of activated factor XII with a single bolus injection of recombinant human albumin-fused Infestin-4 on the release of bradykinin, the brain lesion size, and contact-kinin system-dependent pathological events. We determined protein levels of bradykinin, intracellular adhesion molecule-1, CC-chemokine ligand 2, and interleukin-1β by enzyme-linked immunosorbent assays and mRNA levels of genes related to inflammation by quantitative real-time PCR. Brain lesion size was determined by tetrazolium chloride staining. Furthermore, protein levels of the tight junction protein occludin, integrity of the blood-brain barrier, and brain water content were assessed by Western blot analysis, extravasated Evans Blue dye, and the wet weight-dry weight method, respectively. Infiltration of neutrophils and microglia/activated macrophages into the injured brain lesions was quantified by immunohistological stainings. Results We show that both genetic deficiency of factor XII and inhibition of activated factor XII in mice diminish brain injury-induced bradykinin release by the contact-kinin system and minimize brain lesion size, blood-brain barrier leakage, brain edema formation, and inflammation in our brain injury model. Conclusions Stimulation of bradykinin release by activated factor XII probably plays a prominent role in expanding secondary brain damage by promoting brain edema formation and inflammation. Pharmacological blocking of activated factor XII could be a useful therapeutic principle in the treatment of TBI-associated pathologic processes by alleviating posttraumatic inflammation and brain edema formation.